Fair Trade Altruism, or Egoism? - Pánek, Martin; Chalupníček, Pavel; Petrášek, František, 1934-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2010)
This bachelor thesis discusses the issue of Fair Trade. It tries to solve the question whether Fair Trade is an altruistic, or an egoistic phenomenon. The thesis explains how the author understands the terms "altruism" and "egoism" and then describes the methodology used to distinguish between the two. Special attention is paid to the problem of information asymmetry and how Fair Trade is specific in this respect. The thesis largely discusses Fair Trade as development aid and questions the effectiveness of this particular kind of development aid; it clarifies what role the problem of altruism plays in it. This thesis also discusses the issue of public choice related to the main topic. It reviews some examples of public decisions and links them back to the question of altruism. Using standard microeconomic analysis, the thesis is concluded with a statement on altruism or egoism behind Fair Trade.
Vedoucí práce: Pavel Chalupníček
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2010
Rok obhajoby 2010
Keywords: národní hospodářství [obor bakal. práce]; bakalářské práce; bachelor's theses